2020
DOI: 10.21203/rs.3.rs-33873/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epidemiological approximation of the enteric manifestation and possible fecal-oral transmission in COVID-19: A preliminary systematic review

Abstract: Objectives: to conduct a systematic review to describe the epidemiological scientific evidence on gastrointestinal symptoms (GIS), enteric involvement and fecal excretion of SARS-CoV-2 viral RNA and to discuss the possible fecal-oral transmission pathway of COVID-19.Methods: We have reviewed GIS, enteric involvement, and fecal test results of SARS CoV-2 from case reports and retrospective observational studies related to the digestive system published about the outbreak.Results: The prevalence of GIS in patien… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…In fact, Huang et al (2020) reported that GI involvement was present in 2–10% of patients with COVID-19. A systematic review evaluating GI involvement reported that the presence of GI symptoms had a great variability between 2 and 100%; in particular, according to a pooled analysis, 16.1% presented GIS, 8.3% diarrhea, 12% nausea-vomiting and 4% abdominal pain ( Pamolona et al, 2020 ). Sometimes, GI symptoms may precede respiratory ones ( Wang et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, Huang et al (2020) reported that GI involvement was present in 2–10% of patients with COVID-19. A systematic review evaluating GI involvement reported that the presence of GI symptoms had a great variability between 2 and 100%; in particular, according to a pooled analysis, 16.1% presented GIS, 8.3% diarrhea, 12% nausea-vomiting and 4% abdominal pain ( Pamolona et al, 2020 ). Sometimes, GI symptoms may precede respiratory ones ( Wang et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%
“…This protein, in fact, is expressed in gastric, intestinal and colonic cells, promoting virus infection ( Wan et al, 2020a ). Therefore, once the virus infects the human intestinal epithelia, it can potentially propagate via fecal-oral route ( Wang et al, 2020a ; Guan et al, 2020 ; Pamolona et al, 2020 ). Interesting, viral RNA is detected in the stool for a longer time than in the respiratory system ( Pan et al, 2020 ; Wu et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the common presenting symptoms of the disease, GI-related complaints are seen in up to 38% of patients, among which diarrhea, nausea/vomiting and abdominal pain are the most common complaints. 43 …”
Section: Discussionmentioning
confidence: 99%
“…First, it is possible the active viral burden is increased by a high stomach pH. This would allow intact virus to travel to the small intestine and gain entry through gut epithelial cells [ 52 ]. Diarrhea and abdominal discomfort can be symptoms of COVID-19 [ 53 ].…”
Section: The Role Of the Stomach In Mitigating Covid-19mentioning
confidence: 99%